Creating a Blended Learning Model for Online Learning System in Indonesia - Anis Chaeruman, Uwes; Wibawa, Basuki; Syahrial, Zulfiati (International Journal of Engineering and Technology, 2018)
Online system born out of technological advances benefits the world of education. This system utilizes the internet to disseminate information and act as a communication tool. The application of Blended Learning is generally able to improve the result of the learning process by changing learning habits and methods in many countries. By involving 7 e-learning instructors and 235 respondents, a formative research was conducted to investigate the increase in learning characteristics, i.e. innovation, compatibility and complexity to determine the appropriate model for the application of Blended Learning in an online learning system (SPADA) in Indonesia. The result of this research can be used as a guideline in the lesson plan design component, learning experience management and the balance interaction between lecturers and students during the learning process.Â Â